Diagnosis of Streptococcus pneumoniae pneumonia by quantitative enzyme linked immunosorbent assay of C-polysaccharide antigen. Issue 8 (August 1994) - Gillespie, S H; Smith, M D; Dickens, A; Raynes, J G; McAdam, K P
Abstract : AIMS–To evaluate the use of a quantitative enzyme linked immunosorbent assay (ELISA) detecting C-polysaccharide (PnC) antigen in sputum for the diagnosis of Streptococcus pneumoniae infection. METHODS–Specimens of sputum from 60 patients with acute community and hospital acquired pneumonia and infective exacerbations of obstructive airways disease were examined by semiquantitative culture and antigen ELISA. RESULTS–Using a cutoff value of 1 microgram/ml PnC antigen for a positive result, the sensitivity of this assay was 90.3%, specificity 93.1%, predictive value of a positive result was 93.5%, and the predictive value of a negative result 89.6%. CONCLUSIONS–Quantitation of C-polysaccharide antigen in sputum by ELISA distinguishes between carriage of oral bacteria which express PnC-like antigen and infection with S pneumoniae and compares favourably with other diagnostic methods.